Automating FYP health check in managing final year project: FYP companion / Zayid Hamdan and Erfan Shukor - Hamdan, Zayid; Shukor, Erfan (Faculty of Computer and Mathematical Sciences, 2021)
Final Year Project (FYP) is a requirement for bachelor’s degree qualification. It is a tool to measure the student’s understanding, skills, and expertise gained throughout their studies. Currently, most students of Bachelor in Information Technology (Hons.) Information Systems Engineering have problems in managing their FYP. Based on a study titled “Implementation of Health Checking Tools using Lean Method for Managing Final Year Project” by Siti Izniwafaa Binti Azizan, shows students having difficulty in monitoring and controlling the process of their FYP which results in ineffective FYP deliverables. Thus, this study aims to develop a web-based application that provides a platform for FYP students to manage and track their project progress. There are two main deliveries in the FYP which are the report and the system itself. This study used a dashboard interface as a technique of reminding the project progress, delivery due dates, and traffic light approach in representing the status of each task and delivery. As a flexibility feature, the project is designed as a responsive web to provide mobility to enable users to access by using mobile web. The system empowers control to students in monitoring the progress of their FYP by allowing them to create their schedule and providing visualization of project health. A notification system was used to remind students when the due dates are around the corner. Besides, the supervisor can monitor the project health and progress of their supervisees during the project execution. Waterfall methodology was implemented to assist the development of this project. With the system implemented Bachelor in Information Technology (Hons.) Information Systems Engineering students can have a systematic tool to assist in monitoring the ‘health’ of their final year project progress.